Processamento de dados sísmicos em uma linha 2D da bacia do Camamu - TAVARES, Carolina Tadaiesky (2019)
The seismic method allows investigations of deep targets with high resolution and has become an important technology in operation hydrocarbons. In the industry of hydrocarbon exploration companies offer special services software for seismic processing, this work we use a package known in exploration industry, which is the Landmark Inc, the ProMAX. An important part of seismic process is the identification and subsequent suppression of multiple reflections to help in the interpretation of true characteristics of the structure in the subsurface. This study aimed to process a set of 2D seismic data, related to basin Camamu and present a strategy for mitigation of multiple subsurface free, which are very common in surveys environment.